ECOLOGICAL DIVERSITY AND AGRICULTURAL INFLUENCES OF RUSSET POTATOES: A COMPREHENSIVE REVIEW - Zmarialay Tani (CV. Radja Publika, 2024)
This comprehensive review paper discovers the ecological diversity and agricultural influence of Russet Potatoes. Russet potatoes are an essential produce with significant economic and nutritional value, characterized by their thick skin and starchy flesh. This review examines the genetic diversity within Russet potato varieties, highlighting their adaptability to various environmental conditions and resistance to pests and diseases. It also delves into the ecological implications of Russet potato cultivation, including soil health, biodiversity, and sustainable farming practices. Furthermore, the review assesses the agricultural influence of Russet potatoes, focusing on yield optimization, economic impact, and their role in global food security. A systematic literature review was conducted to gather comprehensive information on the ecological diversity and agricultural influence of Russet potatoes. By synthesizing current research, this review provides a holistic understanding of the importance of Russet potatoes in modern agriculture and their potential for fostering sustainable agricultural systems.